Mopane worm (Gonimbrasia belina)—An exclusive African edible insect as human food—A comprehensive review - Shahida Anusha Siddiqui; Deepak Kumar Mahanta; Tanmaya Kumar Bhoi; Ali Ahmad; Ito Fernando (Future Foods)
Edible insects have drawn more attention in recent years as a reliable source of nutrition with an opportunity to alleviate a number of issues with the current global food chain. They have the ability to provide small-scale growers and entrepreneurs with economic and livelihood possibilities. As the demand for edible insects rises globally, mopane worms may one day be an important source of nourishment outside of the African regions where they are currently consumed. Mopane worms are attractive as an edible insect due to a number of factors, such as their high nutritional value, minimal environmental impact, and simplicity of cultivation and harvesting, which may increase their sales potential and economic value. Mopane worms provide 58 % protein, 15 % fat, 8 % ash, 8 % carbohydrate, and significant amounts of minerals. The market value of mopane worm is projected to be $2.5–4.0 per kilogram. Mass rearing, gathering, processing, and storage practices that are effective and sustainable can guarantee the safety and quality of products while boosting consumer demand and producer prospects for profit. Mopane worms have an exciting potential as an edible insect, and additional investigation and advancement in these areas may help to realize their full capability as a food source.